Sensing the Polar Atmosphere with GOME and SCIAMACHY - Gottwald, Manfred (2010)
The polar atmosphere is a rather unique environment. Detailed views of the polar atmosphere are essential for understanding the global role of the atmosphere in the Earth system. Due to the remote location of the polar regions large parts of their atmosphere are usually not within reach for ground- or airborne measurements. Only spaceborne remote sensing can provide almost permanent access. In the late 80’s / early 90’s of the past century Europe has initiated its ambitious program of atmospheric Earth Observation absorption spectrometers. These sensors retrieve atmospheric parameters from absorption features in the radiance reflected and scattered off the Earth’s atmosphere. GOME on ERS-2, SCIAMACHY on ENVISAT (both ESA) and GOME-2 on EUMETSAT’s METOP-A, the first of three METOP platforms, are currently operational in orbit. The highly inclined orbits of ERS-2, ENVISAT and METOP-A carry their payloads each day 14-15 times over the arctic and antarctic region thus permitting continuous monitoring of the status of the polar atmosphere. In the past 15 years various phenomena, natural and anthropogenic in origin, have been studied in detail. They range from the troposphere (e.g. BrO plumes in arctic spring) via the stratosphere (annual ozone hole episodes and associated chemistry) up to the mesosphere (e.g. properties of Noctilucent Clouds).